2019
DOI: 10.1128/mbio.01941-19
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Mutagenesis in Phlebotomus papatasi: the Immune Deficiency Pathway Impacts Vector Competence for Leishmania major

Abstract: Sand flies are the natural vectors for the Leishmania species that produce a spectrum of diseases in their mammalian hosts, including humans. Studies of sand fly/Leishmania interactions have been limited by the absence of genome editing techniques applicable to these insects. In this report, we adapted CRISPR (clustered regularly interspaced palindromic repeat)/Cas9 (CRISPR-associated protein 9) technology to the Phlebotomus papatasi sand fly, a natural vector for Leishmania major, targeting the sand fly immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…and Leishmania sp.) showed that the expression of Relish and Cactus regulates infection prevalence and intensity, highlighting the importance of the IMD and Toll pathways in anti-parasitic immune responses in vectors ( Meister et al., 2005 ; Frolet et al., 2006 ; Hu and Aksoy, 2006 ; Antonova et al., 2009 ; Louradour et al., 2019 ). In this regard, a recent report demonstrated a reduction in T. cruzi loads in the midgut of R. prolixus treated with the drug IMD-0354, which impedes the activation of NF-κB TFs ( Vieira C. S. et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…and Leishmania sp.) showed that the expression of Relish and Cactus regulates infection prevalence and intensity, highlighting the importance of the IMD and Toll pathways in anti-parasitic immune responses in vectors ( Meister et al., 2005 ; Frolet et al., 2006 ; Hu and Aksoy, 2006 ; Antonova et al., 2009 ; Louradour et al., 2019 ). In this regard, a recent report demonstrated a reduction in T. cruzi loads in the midgut of R. prolixus treated with the drug IMD-0354, which impedes the activation of NF-κB TFs ( Vieira C. S. et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…numbers in the gut of sand flies. Similarly, the mutagenesis of Rel2 by CRISPR/Cas9 generates a more permissive phenotype in insect vector, presenting higher loads of promastigotes (Telleria et al, 2012;Louradour et al, 2019). Hamilton et al (2015) described that Jaenimonas drosophilae, a trypanosomatid found naturally infecting Drosophila fallen, is able to establish infections in larvae of different species of Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…papatasi and L . longipalpis , aiming to target leishmanial vector competence, has been recently attempted [ 110 ]. Furthermore, Phlebotomus and Lutzomyia species have been found naturally infected with Wolbachia strains [ 111 ], and a potential for the use of Wolbachia , alone or in combination with sterile insect technique, has been indicated [ 112 ].…”
Section: Methodsmentioning
confidence: 99%